Pulmonary Embolism Associated with Hyperemesis Gravidarum Two Case Reports - Keskinkılıç, Bekir; Uygur, Dilek; Özcan, Ayşe; Üstün, Yaprak Engin; Keskin, Hüseyin Levent; Karaahmetoğlu, Selma; Esen, Meral; Şencan, İrfan and Sanisoğlu, Sema (Gynecology Obstetrics & Reproductive Medicine, 2017)
Pulmonary embolism is a major cause of death during pregnancy or the puerperium. The hemostatic changes in pregnancy creates a prothrombotic milieu. Hyperemesis gravidarum is one of the recognised risk factors for venous tromboembolism.Two cases of maternal mortality were attributed to PE associated with severe hyperemesis gravidarum in 2014 in Turkey. These two cases have been reported and discussed in the literature review. We aimed to alert clinicians that thromboprophylaxis should be considered when a pregnant woman suffers vomiting leading to clinical evidence of dehydration.